(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVES: Functional orthodontic devices can modify oral function thus permitting more adequate growth processes. The assessment of their effects should include both facial morphology and muscle function. This preliminary study investigated whether a preformed functional orthodontic device could induce variations in facial morphology and function along with correction of oral dysfunction in a group of orthodontic patients in the mixed and early permanent dentitions. MATERIAL AND METHODS: The three-dimensional coordinates of 50 facial landmarks (forehead, eyes, nose, cheeks, mouth, jaw and ears) were collected in 10 orthodontic male patients aged 8-13 years, and in 89 healthy reference boys of the same age. Soft tissue facial angles, distances, and ratios were computed. Surface electromyography of the masseter and temporalis muscles was performed, and standardized symmetry, muscular torque and activity were calculated. Soft-tissue facial modifications were analyzed non-invasively before and after a 6-month treatment with a functional device. Comparisons were made with z-scores and paired Student's t-tests. RESULTS: The 6-month treatment stimulated mandibular growth in the anterior and inferior directions, with significant variations in three-dimensional facial divergence and facial convexity. The modifications were larger in the patients than in reference children. In several occasions, the discrepancies relative to the norm became not significant after treatment. No significant variations in standardized muscular activity were found. CONCLUSIONS: Preliminary results showed that the continuous and correct use of the functional device induced measurable intraoral (dental arches) and extraoral (face) morphological modifications. The device did not modify the functional equilibrium of the masticatory muscles.